MiRNAs in primary cutaneous lymphomas - Yu, Xin (Cell Prolif, 2015)
Primary cutaneous lymphomas (PCL) compose a heterogeneous disease with still unknown aetiology and mechanisms of development. MicroRNAs (miRNAs) have recently been discovered as one of the crucial players in PCL carcinogenesis through post‐transcriptional regulation of gene expression. miRNAs have been reported to be frequently deregulated in PCLs and their biological significance has been further confirmed in multiple functional experiments. Such studies help us understand molecular pathogenesis of PCL. In this review, we summarize expression of miRNAs and their corresponding roles in different subtypes of PCL. With expression and functional role of miRNAs revealed, investigation of their possible clinical use as biomarkers for diagnosis, prediction of prognosis and target for therapies, will be a promising area in the future.